Research of Species Composition of Bovine Piroplasmosis and its Distribution in the South of Kazakhstan - Kuzerbayeva, Aisulu T.; Baizhanov, Kenes S.; Ermekbayeva, Roza Zh.; Userbai, Askar Zh.; Nurkhojayev, Nurzhan O. (Journal of Buffalo Science, 2024)
Context: The relevance of the stated subject of scientific research is determined by the need for rational planning and timely implementation of therapeutic and prophylactic measures with cattle in different geographical regions to prevent the spread of ticks and develop an objective understanding of the real features of the epizootic situation in these regions. Object: This scientific research aims to explore the species composition of bovine piroplasmosis and its distribution in the Turkestan region of the Republic of Kazakhstan. Methods: This research combines species identification of ixo did ticks with practical examination and regular collection from cattle during the pasture season to determine tick species and pasture tickiness, conducted at Mukhtar Auezov South Kazakhstan University, the regional veterinary laboratory, and farms in the Turkestan region. Results: During this scientific research, practical results were obtained, indicating the main trends in the species composition and development of dynamics of the distribution of Bovine theileriosis on the territory of the Turkestan region. The research results and conclusions are highly significant for livestock farm workers in the Turkestan region of Kazakhstan, aiding in cattle health management and epidemic prevention.